Effectiveness of Direct learning on IPA Learning - Afriani, Kharisty; Gani, Abdul Rafid Fakhrun (Jurnal Ilmiah Mandala Education (JIME), 2025)
The Direct learning model was one of the learning models commonly used in science education; however, it was considered less effective and resulted in monotonous learning. This study aimed to analyze the effectiveness of the Direct learning model in science education. The research was conducted at Muhammadiyah Private Junior High School 1 Medan using an experimental method with a pre-experimental design model of the one-shot case study type. The results of the study showed that Direct learning was not effective for science education, as the calculated t-value of 0.519 was smaller than the t-table value of 1.697. The ineffectiveness of Direct learning was due to its teacher-centered nature, which was unsuitable for science education that required students to be active in the learning process. Therefore, the Direct learning model was not suitable for application in science education.